Self-Care Skills of Children with Moderate Intellectual Disability - Heni Gerda Pesau; Endang Widyorini; Sri Sumijati (Journal of Health Promotion and Behavior, 2020)
Background: Intellectual disability is one of the developmental disorders that showing a delay in self-care skills that need to decrease the physical dependence of children to adults. Children with moderate intellectual disability could show differences in developmental and level of self-care skills that affected of few factors. The aim of the study is to explore the self-care skills of children with moderate intellectual disability on feeding, dressing, toileting, and self-hygiene, and factors that affect these skills.Subjects and Method: This was a qualitative study with case study approach. A total of five subjects with moderate intellectual disability aged 7-12 years was selected for this study. The data were collected from eleven parents and teachers by interview. All data were analyzed by content analysis.Results: All five subjects have different levels of each of the self-care skills and get help from teachers or parents in some of these activities. The amount of help is influenced by internal factors such as physical and motor problems as indicated by observations of subject 2. External factors that are found are parental roles, self-care practicing methods, and differences in parent attitudes. Behavioral problems factor such as aggressive, self-harm, and social withdrawal was not found. Self-care programs and the coordination of parents and school as external factors were only found in subject 2 and 4.Conclusion: All five subjects showed varying abilities of the self-care skills and internal and external factors that affect these skills.Keywords: moderate intellectual disability, self-care skills, factorsCorrespondence: Heni Gerda Pesau. Faculty of Psychology, Universitas Atma Jaya, Makassar. Jl. Tanjung Alang No.23 Makassar, South Sulawesi, Indonesia. Email: henigerda0@gmail.com. Mobile: +6285341916728Journal of Health Promotion and Behavior (2020), 5(1): 43-49https://doi.org/10.26911/thejhpb.2020.05.01.06